Potential of Khaya senegalensis to mitigate epileptogenesis and cognitive dysfunction on kainate-induced post-status epilepticus model - Antoine Kavaye Kandeda; Liliane Yimta Foutse; Stéphanie Lewale; Théophile Dimo (IBRO Neuroscience Reports)
Background and aim: To date, there is no treatment to prevent the development of temporal lobe epilepsy, the most common form of drug-resistant epilepsy. A recent study revealed the antiepileptic-like effect of the aqueous extract of Khaya senegalensis. Given the potential of this extract, the antiepileptogenic- and learning and memory-facilitating-like effects of the aqueous extract of Khaya senegalensis were assessed using the kainate-induced post-status epilepticus model. Methods: Epilepsy was induced by injecting a single dose of kainate (12 mg/kg, i.p.) in rats. Animals that developed 2 hours of status-epilepticus were randomized and treated as follows: a negative control group received distilled water (10 ml/kg, p.o.); two positive control groups received sodium valproate (300 mg/kg, p.o.) or phenobarbital (20 mg/kg, p.o.); and three test groups received the extract (50, 100, 200 mg/kg, p.o.). A sham group was added and received distilled water (10 ml/kg, p.o.). All treatments were performed twice daily until the occurrence of the first spontaneous seizure (stage 4 or 5) in the negative control group, on day 14. After the completion of treatments, memory impairment was assessed using the T-maze. Two weeks following behavioral analysis, the rats that received the most effective dose of the extract on spontaneous recurrent were challenged with pentylenetetrazole (30 mg/kg, i.p.). This is to assess their susceptibility to generalized tonic-clonic seizures (stage 5). Rats were finally euthanized, and pro-inflammatory cytokines, or neurogenesis markers were quantified in the hippocampus. Results: The extract of Khaya senegalensis significantly prevented spontaneous recurrent seizures on day 14. It also reduced cognitive decline. Furthermore, it significantly decreased pro-inflammatory cytokines levels and increased those of neurotrophic factors. Conclusions: These findings thus suggest that the extract is endowed with antiepileptogenic- and learning and memory-enhancing-like effects. These effects are likely mediated by anti-inflammatory and neurotrophic pathways. This justifies, therefore, its use to treat empirically epilepsy.